Inferno : a novel - Brown, Dan, 1964- (New York : Doubleday, 2013)
In the heart of Italy, Harvard professor of symbology Robert Langdon is drawn into a harrowing world centered on one of history's most enduring and mysterious literary masterpieces . . . Dante's Inferno. Against this backdrop, Langdon battles a chilling adversary and grapples with an ingenious riddle that pulls him into a landscape of classic art, secret passageways, and futuristic science.
Keywords: Dante Alighieri, -- 1265-1321. -- Fiction; Langdon, Robert (Fictitious character) -- Fiction; Cryptographers -- Fiction; Mystery fiction